Mutations in Durum Wheat SBEII Genes affect Grain Yield Components, Quality, and Fermentation Responses in Rats. Issue 6 (1st November 2015) - Hazard, Brittany; Zhang, Xiaoqin; Naemeh, Mahmoudreza; Hamilton, M. Kristina; Rust, Bret; Raybould, Helen E.; Newman, John W.; Martin, Roy; Dubcovsky, Jorge
ABSTRACT: Increased amylose in wheat ( Triticum ssp.) starch is associated with increased resistant starch, a fermentable dietary fiber. Fermentation of resistant starch in the large intestine produces short‐chain fatty acids that are associated with human health benefits. Since wheat foods are an important component of the human diet, increases in amylose and resistant starch in wheat grains have the potential to deliver health benefits to a large number of people. In three replicated field trials we found that mutations in starch branching enzyme II genes (SBEIIa and SBEIIb ) in both A and B genomes ( SBEIIa/b ‐AB) of durum wheat [ T. turgidum L. subsp. durum (Desf.) Husn.] resulted in large increases of amylose and resistant starch content. The presence of these four mutations was also associated with an average 5% reduction in kernel weight ( P = 0.0007) and 15% reduction in grain yield ( P = 0.06) compared to the wild type. Complete milling and pasta quality analysis showed that the mutant lines have an acceptable quality with positive effects on pasta firmness and negative effects on semolina extraction and pasta color. Positive fermentation responses were detected in rats ( Rattus spp.) fed with diets incorporating mutant wheat flour. This study quantifies benefits and limitations associated with the deployment of the SBEIIa/b ‐AB mutations in durum wheat and provides the information required to develop realistic strategies to deploy durum wheat varieties with increased levels of amylose and resistant starch.